Transcription Factors in the Cellular Response to Charged Particle Exposure - Hellweg, Christine E.; Spitta, Luis F.; Henschenmacher, Bernd; Diegeler, Sebastian; Baumstark-Khan, Christa (Frontiers in Oncology, 2016)
Charged particles, such as carbon ions, bear the promise of a more effective cancer therapy. In human spaceflight, exposure to charged particles represents an important risk factor for chronic and late effects such as cancer. Biological effects elicited by charged particle exposure depend on their characteristics, e.g., on linear energy transfer (LET). For diverse outcomes (cell death, mutation, transformation, and cell-cycle arrest), an LET dependency of the effect size was observed. These outcomes result from activation of a complex network of signaling pathways in the DNA damage response, which result in cell-protective (DNA repair and cell-cycle arrest) or cell-destructive (cell death) reactions. Triggering of these pathways converges among others in the activation of transcription factors, such as p53, nuclear factor κB (NF-κB), activated protein 1 (AP-1), nuclear erythroid-derived 2-related factor 2 (Nrf2), and cAMP responsive element binding protein (CREB). Depending on dose, radiation quality, and tissue, p53 induces apoptosis or cell-cycle arrest. In low LET radiation therapy, p53 mutations are often associated with therapy resistance, while the outcome of carbon ion therapy seems to be independent of the tumor’s p53 status. NF-κB is a central transcription factor in the immune system and exhibits pro-survival effects. Both p53 and NF-κB are activated after ionizing radiation exposure in an ataxia telangiectasia mutated (ATM)-dependent manner. The NF-κB activation was shown to strongly depend on charged particles’ LET, with a maximal activation in the LET range of 90–300 keV/μm. AP-1 controls proliferation, senescence, differentiation, and apoptosis. Nrf2 can induce cellular antioxidant defense systems, CREB might also be involved in survival responses. The extent of activation of these transcription factors by charged particles and their interaction in the cellular radiation response greatly influences the destiny of the irradiated and also neighboring cells in the bystander effect.